ANALYSIS OF CUSTOMER SATISFACTION WITH DRUG PURCHASE SERVICES AT HALODOC - Musnelina, Lili; Refdanita, Refdanita; Pontoan, Jenny; Ivana, Cornelia (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2024)
The swift progress of technology and information in contemporary times opens up avenues for expanding marketing networks, introducing novel products or services, and seamlessly integrating online activities. Online platforms for pharmaceutical sales streamline the process for consumers, offering convenience in finding desired medications at competitive prices and ensuring swift access. This study aims to assess customer contentment concerning the caliber of pharmaceutical procurement services offered through the Halodoc app. Through purposive sampling, data collection was conducted via questionnaires administered to 422 Halodoc users capable of assessing service quality. Utilizing the E-service quality (e-CSI) methodology for analysis, consumer satisfaction with drug purchasing services was measured. Findings revealed high satisfaction levels across various dimensions: reliability at 97.40%, responsiveness at 91.10%, guarantee at 92.06%, empathy at 82.90%, and physical evidence at 91.28%, culminating in an overall Customer Satisfaction Index (CSI) score of 90.98%. Hence, it can be inferred that respondents utilizing the Halodoc application expressed significant satisfaction with the service provided.